Pengaruh Etos Kerja, Iklim Kerja Dan Motivasi Kerja Terhadap Prestasi Kerja Karyawan Warung Padang Upik Yogyakarta - Ocsalino Damare; Prayekti Prayekti; Epsilandri Septyarini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study was to determine the effect of work ethic, work climate, and work motivation on employee performance. This study used a questionnaire as a data collection tool and multiple linear regression as a data analysis tool. The research sample is 50 with saturated sampling technique. The findings of the research are stimulants that the independent variables, namely, work ethic, work climate and motivation have a positive and significant effect on the dependent variable, namely work performance.